2013
DOI: 10.2752/175303713x13795775536174
|View full text |Cite
|
Sign up to set email alerts
|

Looking After Chronically III Dogs: Impacts on the Caregiver's Life

Abstract: Studies in human medicine show that care of chronically ill family members can affect the caregiver's life in several ways and cause "caregiver burden." Companion animals are offered increasingly advanced veterinary treatments, sometimes involving home care. Owners choosing such treatments could thus face similar challenges when caring for their animals. This qualitative study uncovers impacts on an owner's life, when attending to the care of an aged or chronically ill dog and reflects on the differing roles o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
68
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(78 citation statements)
references
References 42 publications
2
68
0
Order By: Relevance
“…The impact experienced by owners was greater than anticipated by the investigators, although elements relating to stress, limitations and di culty sleeping have been noted in previous literature regarding animals with chronic illnesses (17,18), and parents of children with epilepsy (27). However, this study provides greater understanding of areas of importance with regards to canine idiopathic epilepsy speci cally, and also highlights the complexity of the issues experienced by owners.…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…The impact experienced by owners was greater than anticipated by the investigators, although elements relating to stress, limitations and di culty sleeping have been noted in previous literature regarding animals with chronic illnesses (17,18), and parents of children with epilepsy (27). However, this study provides greater understanding of areas of importance with regards to canine idiopathic epilepsy speci cally, and also highlights the complexity of the issues experienced by owners.…”
Section: Discussionmentioning
confidence: 61%
“…However, this study provides greater understanding of areas of importance with regards to canine idiopathic epilepsy speci cally, and also highlights the complexity of the issues experienced by owners. Previous research found that owners of chronically ill animals can feel helplessness when clinical signs are not controlled, and this seems common in owners of dogs with idiopathic epilepsy when seizures are not adequately controlled by anti-seizure drugs (17). However, another recent study found that composite scores for quality of life of dogs with epilepsy and their owners were generally positive (7).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Caregiver burden, a response of strain in the context of providing care for a loved one with an illness, is qualitatively reported by pet caregivers, with approximately half of owners providing care for seriously ill companion animals demonstrating quantitatively increased levels of burden . This caregiver burden is correlated with clinically meaningful clinical signs of depression and reduced quality of life in samples of social media‐recruited companion animal owners and small animal veterinary clinic clients, with owners of a chronically or terminally ill cat or dog being about twice as likely to describe increased clinical signs of depression and high stress levels compared to owners of a healthy pet.…”
Section: Introductionmentioning
confidence: 99%